3 hours a day : how entrepreneurs can multiply their income by working less and living more - Williams, Knolly (McGraw Hill, 2023)
"Williams, also known as The Business Healer, shows you how to transform your work life in a proven 7-step process that includes prioritizing dollar-producing activities while relegating non-dollar producing activities to your capable crew. You'll also learn how to take a dive deep into your own business to find out what's working and what's not, through the 8 Pillars of Success: mindset, activities, people, systems, tools, money, accountability, and training"--